Two new species of Carex (Cyperaceae) from northern South America - Jiménez-Mejías, Pedro; Roalson, Eric H. (Phytotaxa, 2016)
We describe and illustrate two new species of Carex from northern South America. Carex via-incaica from Ecuador belongs to section Aciculares. Carex haematopus from Colombia belongs to section Carex. Both species are so far known only from their type localities.